A participação feminina nos grupos de pesquisa sobre tecnologia da informação no Brasil - Oliveira, Jussara Ribeiro de (2017)
Female segregation in studies and in the performance of Science and Technology is historical and marked by gradual progress and full of mishaps, within this history there are still few studies that deal specifically with this reality in the performance of Information Technology. With the objective of ascertaining how women's participation in the scientific research of Information Technology in Brazil is manifested and if there are any asymmetries, through an analysis of the data of the groups of the Directory of Research Groups of the National Council of Scientific and Technological Development, an exploratory and descriptive research was carried out, through the quantitative approach of the bases of the Directory of Research Groups and the Lattes Curriculum. The result of this analysis points to gender asymmetries and confirms the hypotheses of horizontal and vertical segregation in the scientific research of Information Technology reported in the literature pointed by the studies of gender and feminist epistemology. The results still suggest that Information Technology can be a multidisciplinary field of research. Finally, it is concluded that there are still many challenges to be overcome by women seeking to work in Information Technology and in other fields of Science, Technology, Engineering and Mathematics in Brazil and studies with this subject are crucial to encourage the change of this reality.